A study of intelligibility of five varieties of Indian Englishes to speakers of other varieties of Englishes and its implications on pronunciation teaching - Chacko, Mariam (2015)
Abstract The global spread of Englishes and accent discrimination has brought the topics of intelligibility and nativeness to the forefront. Indian English is one of the varieties of World Englishes that has developed. This study collected five samples of different varieties of Indian Englishes and tested the intelligibility of those utterances to speakers of other varieties of Englishes using the mixed methods approach. After the samples were collected the speakers went through an unstructured interview where they described how they learnt English pronunciation and how they use it. These samples were used in an intelligibility test with listeners from 16 different varieties of Englishes, which included comprehensibility and accentedness ratings as well. This is followed by an interview where these 16 listeners described their reactions to the utterances. The intelligibility scores, comprehensibility and accentedness ratings were then analyzed, keeping in mind how the speakers learnt pronunciation and how the listeners reacted to it. The results were similar to previous studies were suprasegmentals, segmentals and speaking rate were found to be important for intelligibility. These results were used to make recommendations for pronunciation instruction in India.